2016
DOI: 10.1007/s11064-016-1983-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GnRH on Neurite Outgrowth, Neurofilament and Spinophilin Proteins Expression in Cultured Spinal Cord Neurons of Rat Embryos

Abstract: It has been previously described the presence of GnRH receptor in spinal cord neurons of rat embryos and adult rats. However, the functional role of these receptors has not been studied. In this work, the effect of GnRH on neurite outgrowth and cytoskeletal protein expression in cultured spinal cord neurons of rat embryos was analyzed. Specifically, neurofilaments of 68 and 200 kDa by immunoblot assays and spinophilin mRNA expression by RT-PCR. Results show that GnRH stimulates neurite outgrowth in addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In rat embryos, Quintanar et al [ 154 ] studied the effects of GnRH on neurites and upon 68 and 200 kDa neurofilament expression in spinal cord neurons in culture; in addition, changes in spinohilin gene expression were also determined (spinophilin is considered a marker of synaptic contact). The results showed that GnRH stimulates neurite outgrowth ( Figure 1 A,B) in addition to an increase in neurofilaments and spinophilin expression.…”
Section: Expression and Neurotrophic Effects Of Gnrh In The Cnsmentioning
confidence: 99%
“…In rat embryos, Quintanar et al [ 154 ] studied the effects of GnRH on neurites and upon 68 and 200 kDa neurofilament expression in spinal cord neurons in culture; in addition, changes in spinohilin gene expression were also determined (spinophilin is considered a marker of synaptic contact). The results showed that GnRH stimulates neurite outgrowth ( Figure 1 A,B) in addition to an increase in neurofilaments and spinophilin expression.…”
Section: Expression and Neurotrophic Effects Of Gnrh In The Cnsmentioning
confidence: 99%
“…It is possible that the effects obtained by LA administration are due to the activation of receptors for GnRH present in the spinal cord. Previously, the presence of GnRH receptors in spinal cord neurons in animal models such as sheep (Dolan et al 2003) and rat (Quintanar et al 2007) has been described, and these receptors respond to stimulation with GnRH (Quintanar et al 2016a). Once the receptors are activated, biochemical, morphological and functional changes could be generated in the injured nervous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Once the receptors are activated, biochemical, morphological and functional changes could be generated in the injured nervous tissue. In relation to biochemical changes, it has been described that GnRH, or its analogue LA, induces an increase in the expression of neuronal regeneration marker proteins such as 68 and 200 kDa neurofilaments and spinophilin in spinal cord neurons of rat in vivo (Calderón-Vallejo and Quintanar 2012) and in vitro (Quintanar et al 2016a). Likewise, LA induces an increase in myelin basic protein expression, a principal constitutive protein of myelin in oligodendrocytes of spinal cord in a model of multiple sclerosis (Guzmán-Soto et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with GnRH or leuprolide acetate (LA), a GnRH agonist, favored the increase of outgrowths, and the length of neurites in studies with cell cultures of cortical neurons and spinal cord from rat embryos. 150,151 Currently, GnRH agonists are used for the treatment of central precocious puberty, endometriosis, polycystic ovary syndrome, infertility in men, alterations in GnRH secretion, and in the treatment of breast cancer and prostate. 152 Compared with GnRH, the GnRH agonists have a higher affinity for the GnRH receptor and is more resistant to enzymatic degradation and has a powerful effect.…”
Section: Gonadotropin-releasing Hormone Agonistsmentioning
confidence: 99%